2016
DOI: 10.21608/adjalexu.2016.59172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intrinsic Color Stability of Facial Silicone Elastomer Reinforced With Different Nanoparticles

Abstract: INTRODUCTION: Maxillofacial defects are located in a highly visible body area that is identified with one's identity. An aesthetic and comfortable maxillofacial prosthesis relieves many concerns of the patient and may improve quality of life. Silicone elastomers are more color stable than other materials used in maxillofacial prostheses thus many authors investigated the color stability of those materials under weathering conditions. OBJECTIVES: This study evaluates the effects of two types of nano-oxides part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…This could also be influenced by the interaction between TiO 2 nanoparticles and the chemical components of sweat [38]. Notably, finer nanoparticles tend to have a more profound interaction with the silicone's polymeric chain [70]. These insights align with Radey et al's [34] research.…”
Section: Tensile Strengthsupporting
confidence: 70%
“…This could also be influenced by the interaction between TiO 2 nanoparticles and the chemical components of sweat [38]. Notably, finer nanoparticles tend to have a more profound interaction with the silicone's polymeric chain [70]. These insights align with Radey et al's [34] research.…”
Section: Tensile Strengthsupporting
confidence: 70%
“…The first of these conditions was storage in a commercial antibacterial silicone-cleaning solution (B-200-12, Daro Inc., Lakeside, AZ, USA) for thirty hours. The second condition was storage in a simulated sebum solution for six months; the sebum was prepared by dissolving 10% palmitic acid with 2% glyceryl tripalmitate in 88% linoleic acid (all w/w ) [ 30 , 40 , 41 , 42 ]. The third condition was storage in simulated acidic perspiration (sweat) for six months; the sweat was prepared according to the specifications of the International Organization for Standardization (ISO 105-E04:96) [ 43 ] and comprised the following components (per liter of distilled water): 0.5 g of L-histidine monohydrochloride monohydrate, 5 g of sodium chloride, and 2.2 g of sodium dihydrogen orthophosphate dehydrate [ 30 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The second condition was storage in a simulated sebum solution for six months; the sebum was prepared by dissolving 10% palmitic acid with 2% glyceryl tripalmitate in 88% linoleic acid (all w/w ) [ 30 , 40 , 41 , 42 ]. The third condition was storage in simulated acidic perspiration (sweat) for six months; the sweat was prepared according to the specifications of the International Organization for Standardization (ISO 105-E04:96) [ 43 ] and comprised the following components (per liter of distilled water): 0.5 g of L-histidine monohydrochloride monohydrate, 5 g of sodium chloride, and 2.2 g of sodium dihydrogen orthophosphate dehydrate [ 30 , 40 , 41 , 42 ]. The fourth group of specimens was subjected to exposure to accelerated weathering with artificial ultraviolet (UV) radiation for 720 h. This was facilitated by an accelerated UV aging chamber equipped with two lightbulb fixtures positioned directly above the specimens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The outcome supports the finding of Kiat-Amnuay et al, 29 who demonstrated that the intrinsic coloring and opacifiers in a MDX4-4210 silicone could protect color change over time, as did Han et al, 31 who found that filling nano oxides (nano-CeO 2 and 2 and 2.5% nano-TiO 2 ) into facial silicone did help to improve color stability of silicone A-2186. But Nada et al 32 found contrast results as they demonstrated that nanoparticle groups exposed to UV light increased in color change compared with the control, and the more the concentration of nanoparticles, the more the color changed. A possible explanation for this could be that the concentration of nanoparticles in their study was too high (≥2%) which increased the agglomeration resulting in the weak distribution in the elastomer matrix.…”
Section: Effect Of Nano Zinc Oxide Particles On Color Stability Of Famentioning
confidence: 98%